Method for preparing sodium sulfide by catalytically reducing industrial sodium sulfate through vanadium-titanium composite system
By using vanadium-titanium composite system catalyst for catalytic reduction reaction, the problems of high pollution, high energy consumption and low product purity in the preparation process of industrial sodium sulfate are solved, and the low temperature and efficient conversion of industrial sodium sulfate to sodium sulfide is achieved, with high product purity and stable mass percentage content.
Patent Information
- Application Number
- CN202411962655.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, the sodium sulfide preparation process of industrial sodium sulfate has problems such as high pollution, high energy consumption, low product purity and production difficulties caused by the formation of eutectic materials, making it difficult to achieve large-scale, low-cost and efficient resource utilization.
The vanadium-titanium composite system catalyst is used to mix the pulverized and dried industrial sodium sulfate and the vanadium-titanium composite system catalyst to carry out catalytic reduction reaction in the gas-solid fluidized bed to form a sodium sulfide solution.
It realizes the low temperature and high efficiency conversion of industrial sodium sulfate into sodium sulfide, the product has high purity and stable mass percentage content at about 90%, reducing production costs and energy consumption and simplifying the process flow.
Smart Images

Figure CN119503734A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical metallurgy and environmental protection, and more specifically to a method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system. Background Art
[0002] Industrial sodium sulfate, commonly known as Glauber's salt, is mainly composed of sodium sulfate containing crystal water. It is a chemical metallurgical solid waste with huge by-products. At present, there is no large-scale, low-cost and efficient comprehensive utilization technology for solid waste sodium sulfate. A large amount of solid waste can only be stored and treated, which has caused huge environmental pressure on enterprises. Sodium sulfide, as an inorganic compound, is widely used in dyes, printing and dyeing, papermaking, textiles, leather making, electroplating, pharmaceuticals, mineral flotation, sewage treatment and other industries. If industrial sodium sulfate can be converted into sodium sulfide, it can achieve "turning waste into treasure", which is an important way to utilize industrial waste salt resources and even high-value utilization.
[0003] At present, the methods for preparing sodium sulfide from sodium sulfate mainly include coal powder reduction method, barium sulfate by-product method, alkali solution absorption of hydrogen sulfide method and gas reduction method. Among them, coal powder reduction method is the most widely used, and the sodium sulfide output of this method accounts for more than 95% of the total output.
[0004] The coal powder reduction method is to mix solid waste sodium sulfate with coal powder in a certain proportion, calcine under high temperature conditions to generate crude sodium sulfide, then hot dissolve and leach to obtain sodium sulfide solution, and then go through processes such as impurity removal, precipitation, evaporation and concentration to make industrial sodium sulfide. However, the traditional coal powder reduction process uses coal powder as a combustion heat source and reducing agent, and the production process is highly polluting and energy-intensive. In addition, the crude sodium sulfide contains a high content of coal ash, which is difficult to separate and purify. The final sodium sulfide product has a content of about 60%, which is industrial-grade sodium sulfide.
[0005] The barium sulfate by-product method is to convert natural barite ore into barium sulfide by calcining coal, and then reacting with sodium sulfate to produce precipitated barium sulfate and by-product sodium sulfide. However, this method is aimed at preparing high-value-added precipitated barium sulfate, using coal as a combustion heating agent and reducing agent. The impurity content in the by-product is high, which makes it difficult to purify and recover sodium sulfide, and the processing cost is high. It is difficult to use it as a commercial way to produce sodium sulfide. At the same time, the industrial process of this process is relatively complicated, and a series of subsequent treatments of the solution are required, which requires a large investment.
[0006] The alkali solution absorption hydrogen sulfide method is to subject the hydrogen sulfide discharged from the discharge process to purification and impurity removal processes such as acid washing, water washing, gas-liquid separation, etc., and then enter the absorption process, absorb it with sodium hydroxide solution, and evaporate and concentrate it to obtain the sodium sulfide product. This process can not only make full use of the hydrogen sulfide in the tail gas emissions, but also obtain a high-value sodium sulfide product as a by-product. However, the alkali solution absorption hydrogen sulfide method for preparing alkali sulfide is usually a by-product of caustic soda manufacturers, and it is difficult to set up an industrial production line alone.
[0007] Gas reduction is divided into catalytic reduction and non-catalytic reduction, in which non-catalytic reduction directly uses hydrogen or carbon monoxide gas as a reducing agent to directly reduce sodium sulfate to sodium sulfide at high temperature. However, in this process, if the temperature is too low, the reduction reaction is difficult to proceed; if the temperature is too high, exceeding the eutectic temperature (664°C), a mixed crystal eutectic will be formed, and a eutectic layer will be formed on the surface of the reactants. A layer of eutectic hinders the direct contact between the reducing gas and the reactants, thereby inhibiting the further progress of the reaction. The formation of eutectic materials is a major obstacle in the process of industrialization. It will not only cause the material to lose its fluidization characteristics, affecting its uniform distribution and flow performance, but also form deposits in the reactor or the conveying pipeline, causing it to stick to the pipe and clog the pipe, corroding the pipe wall. To this end, a study has also disclosed a method for preparing sodium sulfide by direct gas reduction of molten sodium sulfate, which is to first heat industrial sodium sulfate to a molten state, and then introduce a reducing gas to carry out a gas-liquid reduction reaction. This method can effectively avoid the occurrence of material adhesion during gas-solid reduction. However, the gas-liquid contact effect is poor, the production efficiency is low, and the sodium sulfate-sodium sulfide melt has high requirements on equipment and is difficult to operate.
[0008] The gas catalytic reduction method uses a gas containing hydrogen or carbon monoxide as a reducing agent to directly reduce sodium sulfate and a catalyst to sodium sulfide at high temperature. Preliminary research mainly focuses on the effect of different transition metal oxides on the reduction efficiency during hydrogen reduction, such as Fe2O3, NiO, V2O5, Co2O3, Fe3O4, elemental Ni, TiO2, etc. These metal oxides can reduce the temperature of the gas-solid reduction reaction to the range of 570-650°C. At 570°C, the conversion rate is low and the reduction rate is slow. Among them, α-Fe2O3 can achieve a conversion rate of more than 90% at 610°C and within 240 minutes. The purity content of the product detected by chemical method can also reach more than 90%. It is a more promising catalyst at present, but from the perspective of energy consumption, there is still room for development.
[0009] To this end, for the process of gas catalytic reduction of industrial sodium sulfate, we are committed to developing new catalysts to prevent the formation of eutectic materials without affecting product quality, or setting up new process flows to reduce the impact of eutectic materials, thereby improving the overall level of the sodium sulfide industry. This is the key to achieving large-scale and efficient resource utilization of industrial sodium sulfate in my country. Summary of the invention
[0010] In view of this, the purpose of the present invention is to provide a method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate with a vanadium-titanium composite system, so as to solve the deficiencies in the prior art.
[0011] In order to achieve the above object, the present invention adopts the following technical solution:
[0012] A method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system, specifically comprising the following steps:
[0013] (1) firstly crushing industrial sodium sulfate, and then removing crystal water by drying or heating to obtain anhydrous sodium sulfate for standby use;
[0014] (2) dissolving ammonium metavanadate (NH3VO4) in deionized water, continuously stirring with a magnetic force, and gradually adding an oxalic acid solution to obtain a vanadium precursor solution; after the color of the vanadium precursor solution changes to bright orange, adding titanium dioxide (TiO2) powder to obtain a mixed slurry; continuously stirring the mixed slurry, heating to evaporate water, drying, and calcining to obtain a vanadium-titanium composite catalyst;
[0015] (3) grinding and mixing anhydrous sodium sulfate and a vanadium-titanium composite catalyst, purging with nitrogen, introducing a reducing gas for catalytic reduction, and cooling to room temperature to obtain a reduced product;
[0016] (4) dissolving the reduction product in distilled water, separating the vanadium-titanium composite catalyst by filtration, and obtaining a sodium sulfide solution.
[0017] Furthermore, in the above step (1), industrial sodium sulfate is derived from sodium-based dry flue gas desulfurization solid waste.
[0018] The further beneficial effect of adopting the above is that the sodium-based dry flue gas desulfurization solid waste selected by the present invention is mainly composed of Na2SO4 through X-ray diffraction analysis, and further semi-quantitative analysis combined with X-ray fluorescence spectrometer shows that its Na2SO4 content reaches more than 80%, and no further impurity removal is required, and it can be directly used, simplifying the process and reducing operating costs. The present invention directly uses industrial sodium-based dry flue gas desulfurization ash as raw material, which is cheap and easy to obtain, and omits pretreatment links such as evaporation crystallization and drying, reduces energy consumption, and saves production costs.
[0019] Furthermore, in the above step (1), the drying equipment is an oven, the temperature is 120°C; the heating temperature is 200°C, the gas atmosphere is nitrogen, and the time is 2h.
[0020] Furthermore, in the above step (2), the temperature of the deionized water is 60° C.; the concentration of the oxalic acid solution is 1 mol / L, and the pH value of the solution added to the system is 2.5.
[0021] Furthermore, in the above step (2), the mass fraction of vanadium in the mixed slurry is 10%-25%, preferably 10%, 15%, 20% or 25%, and more preferably 15%.
[0022] Furthermore, in the above step (2), the continuous stirring temperature is 60°C and the time is 1 hour; the temperature is raised to 80°C; the drying equipment is a convection oven, the temperature is 110°C, and the time is more than 12 hours; the calcination equipment is a muffle furnace, the heating rate is 5°C / min, the calcination temperature is 500°C, and the time is 4 hours.
[0023] The above further beneficial effect is that the method adopted by the present invention is the simplest and most convenient impregnation method, which mainly involves dissolving a vanadium precursor in deionized water, dispersing titanium in the vanadium precursor, stirring and impregnating for a period of time, and calcining in an air atmosphere after drying to obtain a vanadium-titanium composite system catalyst. The catalyst can realize the low-temperature and efficient conversion of industrial sodium sulfate into sodium sulfide in a relatively stable reducing atmosphere at a relatively low temperature and in a relatively short reduction time, and the preparation conditions of the catalyst are simple, the operation is simple, and the preparation cycle is short.
[0024] Furthermore, in the above step (3), the mass of vanadium in ammonium metavanadate is 10%-25% of the mass of titanium dioxide powder.
[0025] Furthermore, in the above step (3), the nitrogen purge time is 30 minutes.
[0026] A further beneficial effect of the above method is that an oxygen-free environment is created by nitrogen purging.
[0027] Furthermore, in the above step (3), the reducing gas is at least one of coke oven gas, blast furnace gas, converter gas and water gas, and the corresponding flow rate is 60 mL / min; the catalytic reduction equipment is a gas-solid fluidized bed; the catalytic reduction temperature is 550-750°C, preferably 550-630°C, and more preferably 630°C; the catalytic reduction time is 0.5-3.0h, preferably 1.0-2.5h, and more preferably 2.5h.
[0028] A further beneficial effect of adopting the above method is that the reducing gas selected by the present invention can effectively improve the utilization rate of industrial waste gas and reduce production costs.
[0029] Furthermore, in the above step (3), the cooling gas atmosphere is nitrogen.
[0030] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:
[0031] 1. The present invention uses industrial sodium-based dry flue gas desulfurization solid waste as raw material, and prepares sodium sulfide by catalytic reduction of sodium sulfate at low temperature and high efficiency in a stable reducing atmosphere CO, thereby realizing the recycling of solid waste resources and effectively reducing production costs. The reaction conditions are simple, the operation is simple, the reaction products are easy to separate, the resource utilization rate of sodium sulfate is high, and the obtained sodium sulfide product has high purity, and the mass percentage content is stable at about 90%.
[0032] 2. The method of the present invention has the advantages of high resource utilization, simple process flow, good product quality, low production energy consumption and operating cost, and environmental friendliness. It is suitable for large-scale processing of industrial sodium sulfate and has good economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is the XRD pattern of industrial sodium sulfate in Example 1;
[0034] Figure 2 is the XRD pattern of the vanadium-titanium composite catalyst in Example 1;
[0035] Figure 3 It is a graph showing the conversion rate of industrial sodium sulfate reduced to sodium sulfide at different reduction temperatures;
[0036] Figure 4 This is a graph showing the conversion rate of industrial sodium sulfate to sodium sulfide at different reduction times. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] The method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system specifically comprises the following steps:
[0040] (1) firstly crushing industrial sodium sulfate from sodium-based dry flue gas desulfurization solid waste, and then drying it in an oven at 120° C. to remove crystal water, thereby obtaining anhydrous sodium sulfate for later use;
[0041] (2) dissolving ammonium metavanadate in deionized water at 60°C, stirring magnetically continuously, and gradually adding 1 mol / L oxalic acid solution until the pH of the system is 2.5, to obtain a vanadium precursor solution; after the color of the vanadium precursor solution changes to bright orange, adding titanium dioxide powder, wherein the mass of vanadium in the ammonium metavanadate is 15% of the mass of the titanium dioxide powder, to obtain a mixed slurry; first stirring the mixed slurry continuously at 60°C for 1 hour, then heating the mixture to 80°C to evaporate the water, then placing the mixture in a convection oven at 110°C for 12 hours, and finally placing the mixture in a muffle furnace and heating the mixture to 500°C at a rate of 5°C / min for calcination for 4 hours to obtain a vanadium-titanium composite catalyst;
[0042] (3) Anhydrous sodium sulfate and 25% by weight of a vanadium-titanium composite catalyst were ground and mixed thoroughly and then placed in a quartz reaction tube, and the quartz reaction tube was placed in a gas-solid fluidized bed. The temperature was adjusted to 630° C. in a tubular furnace, nitrogen was purged for 30 min, and coke oven gas was introduced at a flow rate of 60 mL / min. Catalytic reduction was carried out for 2.5 h, and the mixture was cooled to room temperature in a nitrogen atmosphere to obtain a reduced product;
[0043] (4) dissolving the reduction product in distilled water, separating the vanadium-titanium composite catalyst by filtration, and obtaining a sodium sulfide solution.
[0044] Example 2
[0045] The method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system specifically comprises the following steps:
[0046] (1) firstly crushing industrial sodium sulfate from sodium-based dry flue gas desulfurization solid waste, and then drying it in an oven at 120° C. to remove crystal water, thereby obtaining anhydrous sodium sulfate for later use;
[0047] (2) dissolving ammonium metavanadate in deionized water at 60°C, stirring magnetically continuously, and gradually adding 1 mol / L oxalic acid solution until the pH value of the system is 2.5, thereby obtaining a vanadium precursor solution; after the color of the vanadium precursor solution changes to bright orange, adding titanium dioxide powder, wherein the mass of vanadium in the ammonium metavanadate is 10% of the mass of the titanium dioxide powder, to obtain a mixed slurry; first stirring the mixed slurry continuously at 60°C for 1 hour, then heating the mixture to 80°C to evaporate the water, then placing the mixture in a convection oven at 110°C for 12 hours, and finally placing the mixture in a muffle furnace and heating the mixture to 500°C at a rate of 5°C / min for calcination for 4 hours, thereby obtaining a vanadium-titanium composite catalyst;
[0048] (3) grinding anhydrous sodium sulfate and 25% by weight of a vanadium-titanium composite catalyst and mixing them thoroughly and evenly, placing them in a quartz reaction tube, and then placing the quartz reaction tube in a gas-solid fluidized bed, adjusting the temperature to 550° C. in a tubular furnace, purging with nitrogen for 30 min, introducing blast furnace gas at a flow rate of 60 mL / min, catalytic reduction for 3 h, and cooling to room temperature in a nitrogen atmosphere to obtain a reduced product;
[0049] (4) dissolving the reduction product in distilled water, separating the vanadium-titanium composite catalyst by filtration, and obtaining a sodium sulfide solution.
[0050] Example 3
[0051] The method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system specifically comprises the following steps:
[0052] (1) firstly crushing industrial sodium sulfate from sodium-based dry flue gas desulfurization solid waste, and then heating it in a nitrogen atmosphere at 200° C. for 2 h to remove crystal water, thereby obtaining anhydrous sodium sulfate for later use;
[0053] (2) dissolving ammonium metavanadate in deionized water at 60°C, continuously stirring with a magnetic stirrer, and gradually adding an oxalic acid solution with a concentration of 1 mol / L until the pH value of the system is 2.5, thereby obtaining a vanadium precursor solution; after the color of the vanadium precursor solution changes to bright orange, adding titanium dioxide powder, wherein the mass of vanadium in the ammonium metavanadate is 25% of the mass of the titanium dioxide powder, to obtain a mixed slurry; first stirring the mixed slurry continuously at 60°C for 1 hour, then heating the mixture to 80°C to evaporate the water, then placing the mixture in a convection oven at 110°C for 12 hours, and finally placing the mixture in a muffle furnace and heating the mixture to 500°C at a rate of 5°C / min for calcination for 4 hours, thereby obtaining a vanadium-titanium composite catalyst;
[0054] (3) Anhydrous sodium sulfate and 25% by weight of a vanadium-titanium composite catalyst were ground and mixed thoroughly and then placed in a quartz reaction tube, and the quartz reaction tube was placed in a gas-solid fluidized bed, the temperature was adjusted to 710° C. in a tubular furnace, nitrogen was purged for 30 min, and converter gas was introduced at a flow rate of 60 mL / min, catalytic reduction was carried out for 0.5 h, and the mixture was cooled to room temperature in a nitrogen atmosphere to obtain a reduced product;
[0055] (4) dissolving the reduction product in distilled water, separating the vanadium-titanium composite catalyst by filtration, and obtaining a sodium sulfide solution.
[0056] Performance Testing
[0057] 1. Physical and chemical characterization analysis
[0058] The industrial sodium sulfate and vanadium-titanium composite catalyst in Example 1 were subjected to physical and chemical characterization analysis, wherein the structure of the relevant crystalline material was determined by a D / MAX-2200 X-ray diffractometer, CuKa ray (λ=0.15406nm), voltage 40kV, current 40mA, scanning range 10-80°, scanning speed 5° / min.
[0059] The results are as follows Figure 1-2 shown.
[0060] Depend on Figure 1 It can be seen that the main phase of the industrial sodium sulfate (desulfurization ash) in Example 1 is Na2SO4, its crystal form is relatively good, and almost no diffraction peaks of other impurities are observed.
[0061] Depend on Figure 2 It can be seen that the diffraction peak of TiO2 in the vanadium-titanium composite system catalyst of Example 1 is the main peak, and some weaker V2O5 crystal peaks can also be observed.
[0062] 2. Conversion rate of industrial sodium sulfate
[0063] Taking Example 1 as the operation basis, the mass of vanadium in ammonium metavanadate is set to 0, 10%, 15%, 20% and 25% of the mass of titanium dioxide powder, the temperature of catalytic reduction is set to 550°C, 590°C, 630°C, 710°C and 750°C, the time of catalytic reduction is set to 1.0h, 1.5h, 2.0h, 2.5h and 3.0h, and the conversion rate of industrial sodium sulfate at different reduction temperatures and different reduction times is calculated respectively.
[0064] The results are as follows Figure 3-4 shown.
[0065] Depend on Figure 3 It can be seen that the vanadium-titanium composite catalyst of the present invention can achieve a conversion rate of about 90% for desulfurization of industrial sodium sulfate below the eutectic temperature window (664° C.).
[0066] Depend on Figure 4 It can be seen that within a relatively short period of time, the conversion rate of the vanadium-titanium composite catalyst of the present invention to industrial sodium sulfate reaches more than 80%, and energy consumption is significantly improved.
[0067] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system, characterized in that: The specific steps include: (1) firstly crushing industrial sodium sulfate, and then removing crystal water by drying or heating to obtain anhydrous sodium sulfate for standby use; (2) dissolving ammonium metavanadate in deionized water, continuously stirring with magnetic force, and gradually adding oxalic acid solution to obtain a vanadium precursor solution; After the color of the vanadium precursor solution changes to bright orange, titanium dioxide powder is added to obtain a mixed slurry; the mixed slurry is continuously stirred, heated to evaporate water, dried, and calcined to obtain a vanadium-titanium composite system catalyst; (3) grinding and mixing anhydrous sodium sulfate and a vanadium-titanium composite catalyst, purging with nitrogen, introducing a reducing gas for catalytic reduction, and cooling to room temperature to obtain a reduced product; (4) dissolving the reduction product in distilled water, separating the vanadium-titanium composite catalyst by filtration, and obtaining a sodium sulfide solution.
2. The method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system according to claim 1, characterized in that: In step (1), the industrial sodium sulfate is derived from sodium-based dry flue gas desulfurization solid waste.
3. The method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system according to claim 1, characterized in that: In step (1), the drying equipment is an oven at a temperature of 120° C.; the heating temperature is 200° C., the gas atmosphere is nitrogen, and the heating time is 2 hours.
4. The method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system according to claim 1, characterized in that: In step (2), the temperature of the deionized water is 60° C.; the concentration of the oxalic acid solution is 1 mol / L, and the pH value of the oxalic acid solution added to the system is 2.
5.
5. The method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system according to claim 1, characterized in that: In step (2), the mass of vanadium in the ammonium metavanadate is 10%-25% of the mass of the titanium dioxide powder.
6. The method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system according to claim 1, characterized in that: In step (2), the temperature of the continuous stirring is 60°C and the time is 1 hour; the temperature is raised to 80°C; the drying equipment is a convection oven, the temperature is 110°C, and the time is more than 12 hours; the calcination equipment is a muffle furnace, the heating rate is 5°C / min, the calcination temperature is 500°C, and the time is 4 hours.
7. The method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system according to claim 1, characterized in that: In step (3), the amount of the vanadium-titanium composite catalyst used is 25% of the mass of anhydrous sodium sulfate.
8. The method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system according to claim 1, characterized in that: In step (3), the nitrogen purging time is 30 minutes.
9. The method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system according to claim 1, characterized in that: In step (3), the reducing gas is at least one of coke oven gas, blast furnace gas, converter gas and water gas, and the corresponding flow rate is 60 mL / min; the catalytic reduction equipment is a gas-solid fluidized bed, the temperature is 550-750°C, and the time is 0.5-3.0h.
10. The method for preparing sodium sulfide by catalytic reduction of industrial sodium sulfate by a vanadium-titanium composite system according to claim 1, characterized in that: In step (3), the cooling gas atmosphere is nitrogen.